Ectopic Pituitary Adenomas Presenting as Sphenoid or Clival Lesions: Case Series and Management Recommendations - Tajudeen, Bobby A.; Kuan, Edward C.; Adappa, Nithin D.; Han, Joseph K.; Chandra, Rakesh K.; Palmer, James N.; Kennedy, David W.; Wang, Marilene B.; Suh, Jeffrey D. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Background An ectopic pituitary adenoma presenting as a clival or sphenoid mass is a rare clinical occurrence that may mislead the clinician and result in unnecessary interventions or potential medicolegal consequences. Here, we present one of the largest multi-institutional case series and review the literature with an emphasis on radiological findings and critical preoperative workup.Methods Retrospective chart review.Results Nine patients were identified with ectopic pituitary adenomas of the sphenoid or clivus. There were four females and five males. Median age was 60 years old (range, 36–73 years). The most common presenting symptom was headache (56%). Five (56%) patients presented with a mass arising from the clivus while four (44%) presented with a mass in the sphenoid. Six (67%) patients demonstrated biochemical evidence of hypersecretion on full endocrinology panel. All masses showed evidence of enhancement with gadolinium with a propensity for adjacent bone involvement. Lesions also had a predilection for growth toward the cavernous sinus, carotid artery, or sellar floor. Surgical intervention was performed in eight patients (89%). In eight patients (89%), tumors demonstrated immunoreactivity to prolactin.Conclusions Pituitary adenomas can rarely present as an isolated sphenoid or clival mass. Lesions displayed similar magnetic resonance imaging findings with an erosive growth pattern toward the sellar floor, cavernous sinus, or adjacent carotid artery. Patients with clival or parasellar lesions with comparable features should have a preoperative workup which includes prolactin level and alert the physician to consider an ectopic pituitary adenoma in the differential to prevent unnecessary surgery and potential complications.
Keywords: pituitary adenoma; ectopic pituitary tumors; sphenoid tumors; clival tumors